2016
DOI: 10.1063/1.4943165
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Shockley type stacking faults upon forward degradation in 4H-SiC p-i-n diodes

Abstract: The growth of Shockley type stacking faults in p-i-n diodes fabricated on the C-face of 4H-SiC during forward current operation was investigated using Berg-Barrett X-ray topography and photoluminescence imaging. After forward current experiment, Shockley type stacking faults were generated from very short portions of basal plane dislocations lower than the conversion points to threading edge dislocations in the epitaxial layer. The growth behavior of Shockley type stacking faults was discussed. Growth of stack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 33 publications
2
64
0
Order By: Relevance
“…The shape of the expanded 1SSF depends on the Burgers vector of PDs (b PD ). 13) In 1SSF expansion under forward-current operation, a 30°Si-core PD migrates with the formation of the 30°C-core, and as a result, the 1SSF expands with a diamond shape. 10) Regarding 1SSF expansion from the interface between the epitaxial layer and the substrate toward the epitaxial layer surface, the relationship between 1SSF shape and b PD is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of the expanded 1SSF depends on the Burgers vector of PDs (b PD ). 13) In 1SSF expansion under forward-current operation, a 30°Si-core PD migrates with the formation of the 30°C-core, and as a result, the 1SSF expands with a diamond shape. 10) Regarding 1SSF expansion from the interface between the epitaxial layer and the substrate toward the epitaxial layer surface, the relationship between 1SSF shape and b PD is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that 1SSFs expand from BPDs that converted into TEDs near the interface between the epitaxial layer and the substrate. 12,13,19) In our previous study, the original area of 1SSFs expanded by applying forward current to 4H-SiC p-i-n diodes was observed by transmission electron microscopy (TEM) with high spatial resolution. 20) TEM observation has clarified that 1SSF expands into the substrate when high-density minority carriers are injected into the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the knowledge of extended defect formation such as stacking faults (SFs) and twins in the various polytypes is an important issue for use in electronic devices, since these defects can significantly modify the band structure and deteriorate their electronic properties 7,8 . Moreover, 4H/6H SiC‐based devices were found to degrade under operation due to partial Shockley SF formation and expansion 9,10 . As a matter of fact, localized electronic states are generated in the band gap by SFs 11 .…”
Section: Introductionmentioning
confidence: 99%
“…With careful device and contact mask design, we propose that ECCI could even be used to track dislocation evolution in operando. This is a fascinating opportunity to explore the failure mechanisms of semiconductor devices such as GaAs/Si quantum dot lasers [37,38] and GaN [39] and SiC [40] power devices where carrier recombination or electric field-induced dislocation motion is suspected or has been observed postdegradation.…”
mentioning
confidence: 99%